2022
DOI: 10.3390/antiox11030578
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Phytochemicals and Quenching Activity of Radicals in Selected Drought-Resistant Amaranthus tricolor Vegetable Amaranth

Abstract: Leafy vegetables are susceptible to drought stress. Amaranthus tricolor vegetables are resistant to abiotic stress, including drought, and are a source of ample natural phytochemicals of interest to the food industry due to their benefits to consumers’ health. Hence, the selected drought-resistant amaranth genotypes were evaluated for phytochemicals and antioxidant activity in an RCBD study with three replicates. The selected drought-resistant amaranth accessions contained ample carbohydrates, protein, moistur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 69 publications
(46 citation statements)
references
References 50 publications
5
41
0
Order By: Relevance
“…Sarker and Oba [ 150 , 161 ] detected a parallel tendency. Positive and significant correlations were observed with ascorbic acid, TP, AP (DPPH), TF, β-carotene, and AP (ABTS + ), which was corroborative to past results on salt-induced amaranth [ 218 , 219 , 220 , 221 , 222 ]. The positive and noteworthy correlations of ascorbic acid, AP (DPPH), TP, β-carotene, TF, and AP (ABTS + ) suggested that β-carotene, TF, ascorbic acid, and TP had strong AP.…”
Section: Resultssupporting
confidence: 90%
“…Sarker and Oba [ 150 , 161 ] detected a parallel tendency. Positive and significant correlations were observed with ascorbic acid, TP, AP (DPPH), TF, β-carotene, and AP (ABTS + ), which was corroborative to past results on salt-induced amaranth [ 218 , 219 , 220 , 221 , 222 ]. The positive and noteworthy correlations of ascorbic acid, AP (DPPH), TP, β-carotene, TF, and AP (ABTS + ) suggested that β-carotene, TF, ascorbic acid, and TP had strong AP.…”
Section: Resultssupporting
confidence: 90%
“…The increment of pigment displayed a drastic decline in TC and β-carotene. Significant positive relationships of β-carotene and TC with TP, TA (ABTS + and DPPH), and TF recommended that β-carotene and TC displayed a strong capacity to quench radicals which were corroborative of the previous amaranths [ 81 , 82 , 83 ]. β-carotene and TC were associated positively among them.…”
Section: Resultssupporting
confidence: 65%
“…Sodium can be involved in Na-K synergism for the cytokinin-dependent betacyanin synthesis (Elliot, 1979). Sarker et al (2022) also reported that under drought stress conditions, the amount of nutrients in amaranth leaves increases, which is consistent with the recent findings.…”
Section: Discussionsupporting
confidence: 84%